2016
DOI: 10.1158/1538-7445.am2016-ct027
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT027: A phase I, open-label study of GSK3174998 administered alone and in combination with pembrolizumab in patients (pts) with selected advanced solid tumors (ENGAGE-1)

Abstract: Background: OX40 (CD134) belongs to the tumor necrosis factor receptor (TNFR) family, and transduces a costimulatory signal during T-cell activation. In the periphery, OX40 expression is limited to recently activated CD4+ and CD8+ cells. In tumors, infiltrating T lymphocytes are enriched for OX40, where it augments T-cell activation, proliferation and survival. OX40 is also expressed on tumor infiltrating regulatory T cells (Tregs). Intratumoral Treg depletion is critical for the in vivo antitumor activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…In accordance with disappointing clinical trial results, [27][28][29] the clinical candidate human αOX40 IgG2 antibody failed to stimulate TIL proliferation or cytokine secretion in our in vitro expansion assay, while treatment with OX40L resulted in TIL expansion and increased secretion of proinflammatory cytokines. The clinical αOX40 antibody and OX40L differ with regard to their structure: αOX40 antibody is monomeric, whereas OX40L is of hexameric shape.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In accordance with disappointing clinical trial results, [27][28][29] the clinical candidate human αOX40 IgG2 antibody failed to stimulate TIL proliferation or cytokine secretion in our in vitro expansion assay, while treatment with OX40L resulted in TIL expansion and increased secretion of proinflammatory cytokines. The clinical αOX40 antibody and OX40L differ with regard to their structure: αOX40 antibody is monomeric, whereas OX40L is of hexameric shape.…”
Section: Discussionsupporting
confidence: 81%
“…27 Besides, more phase I studies have been performed in which agonistic αOX40 antibody treatment showed low clinical efficacy in advanced solid tumors. 28 29 Hence, we wondered whether the reason for the limited clinical efficacy was due to (1) low OX40 expression on human TILs, (2) minor effects of OX40 costimulation on TIL functions and expansion, or (3) suboptimal performance of the currently used αOX40 antibodies. Therefore, we measured OX40 levels on distinct TIL subsets of colorectal and HCC tumor tissue, thus demonstrating that TI activated T-helper (aTh) and activated regulatory T cell (aTreg) do express high OX40 levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Он трансдуцирует костимулирующий сигнал во время активации Т-клеток. Пациенты с мРМП активно включаются в несколько исследований фазы I, в которых изучаются антагонисты TIM-3 (NCT02608268) [42], ингибиторы LAG3 (NCT01968109) [43] и агонисты OX40 (NCT02528357) [44], с ингибиторами PD-1/PD-L1 и без них. В настоящее время анти-LAG3 mAb (BMS-986016) изучается в сочетании с ниволумабом в исследовании I фазы (NCT01968109) [43].…”
Section: комбинации ингибиторов иммунных контрольных точекunclassified
“…В настоящее время анти-LAG3 mAb (BMS-986016) изучается в сочетании с ниволумабом в исследовании I фазы (NCT01968109) [43]. Агонист OX40 (GSK3174998) исследуется совместно с пембролизумабом в испытании фазы I (NCT02528357) [44]. Еще один интересный подход к стимулированию иммунного ответа дополнительно нацелен на Т-клеточное микроокружение и связан с индоламин-2,3-диоксигеназой, которая является внутриклеточным ферментом, вырабатываемым опухолевыми клетками, и играет важную роль в путях, генерирующих иммуносупрессивные метаболиты [45].…”
Section: комбинации ингибиторов иммунных контрольных точекunclassified